2006
DOI: 10.4319/lo.2006.51.5.1969
|View full text |Cite
|
Sign up to set email alerts
|

A bio-oceanographic filter to larval dispersal in a reef-building coral

Abstract: Gene flow was shown to be limited between western and eastern Caribbean populations of the reef-building coral, Acropora palmata. However, some mixing was detected among populations near Puerto Rico. Our genetic analyses categorize A. palmata samples from the east coast of the Dominican Republic with the western Caribbean population, suggesting a filter to gene flow east of the Dominican Republic. To test the hypothesis of a present day bio-oceanographic filter occurring between Puerto Rico and the Dominican R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
212
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(222 citation statements)
references
References 66 publications
8
212
1
1
Order By: Relevance
“…Most seascape genetic studies have focused on the role of oceanographic factors in determining genetic structure [23][24][25][26][27][28] . The SCB, however, is an oceanographically unique system with heterogeneous and variable mesoscale eddies influencing short-term circulation and the Southern California Cyclonic Gyre dominating longer term circulation patterns 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Most seascape genetic studies have focused on the role of oceanographic factors in determining genetic structure [23][24][25][26][27][28] . The SCB, however, is an oceanographically unique system with heterogeneous and variable mesoscale eddies influencing short-term circulation and the Southern California Cyclonic Gyre dominating longer term circulation patterns 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Significant progress has recently been made in our ability to accurately track pelagic stages (20)(21)(22), as well as in determining genetic connectivity patterns by combining oceanographic models and molecular genetic data (23)(24)(25). However, relatively few empirical studies have investigated how oceanographic conditions influence larval dispersal and ultimately gene flow among marine fishes with varying life-history strategies (7,26,27).…”
mentioning
confidence: 99%
“…Cowen et al (2000) demonstrated the importance of using accurate mortality rates in Lagrangian simulations of larval dispersal using ocean circulation models: higher mortality rates drastically decrease connectivity rates among habitat patches. Those model-derived connectivity probabilities are used to elucidate patterns of gene flow and vicariance (e.g., Baums et al 2006) and population and community dynamics (e.g., Berkley et al 2010, White et al 2010, and they are increasingly used to inform the design and analysis of marine protected areas (e.g., Rassweiler et al 2012, White et al 2013. To date, larval mortality remains a huge uncertainty in those models (Pineda et al 2009), and modelers typically rely on the original estimates of mortality from Rumrill (1990) for parameterization (Vaughn and Allen 2010).…”
mentioning
confidence: 99%